Proposed interior design scheme of Perak Art Gallery at Pusat Perdagangan Greentown, Ipoh, Perak / Nur Hidayah Ibrahim - Ibrahim, Nur Hidayah (Faculty of Architecture, Planning and Surveying, 2011)
The project is to proposed an interior design scheme of Perak Art Gallery for Perak Arts Foundation at Greentown Avenue, Pusat Perdagangan Greentown Ipoh, Perak Darul Ridzuan. The purpose of this project is to design a space for Fine Artitsts to exhibit their artworks and introduce them to the societies. Besides that, the purpose of this project is also to provide an interactive space for art lovers and other societies to meet under one roof and share their thoughts on arts. This project emphasizes on introducing and showcasing the artworks made by local Perak artist, consists of Juhari Said, Abu Bakar Idris, Fauzin Mustafa, Yusri Sulaiman, Nasir Baharuddin, Yeoh Jin Leng, Ramlan Abdullah, Chuah Chong Yong, Ham Rabeah Kamarun, Sharmiza Abu Hasan, Raja Shariman, Shafee Ramli, Saiful Razman Kassim, Raja Azhar, and Raja Zahabuddin. These art intellectuals are among the many fine artists who are experienced and had achieved international recognitions. They use one common source as the medium and concept for their artwork, which is nature.